Land alienation in the Johor Bahru district area: the factors of unsuccessful response of form 5a, national land code 1965 - Hakim, A. M.; Samsudin, S.; Haffiz, A. A. (2021)
Land alienation in Malaysia constitutes an important element in the conduct and governance relating to the National Land Code (NLC) 1965. However, the alienation is within the exclusive jurisdiction of the state authority and the process of such alienation takes too long including to resolve the requirements of Form 5A, NLC 1965. Form 5A is a notice to the applicant to claim the alienation fees which include the quit rent, premium, boundary mark surveying fees, and preparation and registration of documents of title. Although various methods have been taken to manage the issues of Form 5A, there are still lack of response because several internal and external factors. This study investigates the key factors that contribute to unsuccessful of Form 5A in the Johor Bahru District Area. The study conducted by two kind of methods, interviewing 10 respondents and questionnaire distributed to 229 respondents. The results shortlisted 22 factors and narrowed down into four main factors: lack of money, the rates charged are too high, appeal process for premium reduction, extension period and instalment payments. This study is important to balance the property ownership by considering the emerging issues of land alienation for the urban poor.